An evidence-based algorithm for the utility of FDG-PET for diagnosing Alzheimer's disease according to presence of medial temporal lobe atrophy. (May 2016) - Firbank, Michael J.; Lloyd, Jim; Williams, David; Barber, Robert; Colloby, Sean J.; Barnett, Nicky; Olsen, Kirsty; Davison, Christopher; Donaldson, Cam; Herholz, Karl; O'Brien, John T.
Abstract : Background: Imaging biomarkers for Alzheimer's disease include medial temporal lobe atrophy (MTLA) depicted on computed tomography (CT) or magnetic resonance imaging (MRI) and patterns of reduced metabolism on fluorodeoxyglucose positron emission tomography (FDG-PET). Aims: To investigate whether MTLA on head CT predicts the diagnostic usefulness of an additional FDG-PET scan. Method: Participants had a clinical diagnosis of Alzheimer's disease ( n = 37) or dementia with Lewy bodies (DLB; n = 30) or were similarly aged controls ( n = 30). We visually rated MTLA on coronally reconstructed CT scans and, separately and blind to CT ratings, abnormal appearances on FDG-PET scans. Results: Using a pre-defined cut-off of MTLA ⩾5 on the Scheltens (0–8) scale, 0/30 controls, 6/30 DLB and 23/30 Alzheimer's disease had marked MTLA. FDG-PET performed well for diagnosing Alzheimer's disease v. DLB in the low-MTLA group (sensitivity/specificity of 71%/79%), but in the high-MTLA group diagnostic performance of FDG-PET was not better than chance. Conclusions: In the presence of a high degree of MTLA, the most likely diagnosis is Alzheimer's disease, and an FDG-PET scan will probably not provide significant diagnostic information. However, in cases without MTLA, if the diagnosis is unclear, an FDG-PET scan may provide additional clinically useful diagnostic information.